"I Just Want to Do God's Will:" Teaching Martin Luther King, Jr. as a Religious Leader. Issue 1 (2nd January 2018) - Neumann, David
ABSTRACT: Teachers often respond to the perils of teaching about religion by simply avoiding the subject. An investigation of secondary lesson plans on three prominent Martin Luther King, Jr. websites reveals little attention to the ideology of the civil rights movement, especially those touching on religious ideas. Ignoring King's religious views risks fundamentally misrepresenting his identity, his ideology, and his motivation for nonviolence. Stride Toward Freedom: The Montgomery Story, King's 1958 account of the Montgomery Bus Boycott articulates three key features of the theological framework that inspired his activism: the spiritual motivation for his leadership, the ethical basis for his strategy of nonviolent direct action, and the theological understanding of human nature that undergirded his leadership and strategy. These points provide a useful model for introducing King's ideas in the classroom. The effort to intentionally and thoughtfully teach religion could contribute one step toward inculcating genuine tolerance among students. Civil discourse is not fostered simply by identifying core principles everyone shares but also through thoughtful, critical engagement with disparate ideas, including what are, for many people, the most heavily freighted ideas.